PENGARUH PERAN PEMIMPIN TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING - Lavinsa Ngesti Purba; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2016)
Employee performance is influenced by several factors, including the role of leader and motivation. The decline in employee performance due to the role of leader of the unfavorable impact also on the decline in employee motivation in PT . Indo Putra Sejahtera . This study aims to identify and explain the effect of the role of leader on employee performance through motivation as an intervening variable marketing part of PT . Indo Putra Sejahtera . This type of research used explanatory research. The proposed hypothesis that there is a positive and significant influence on the leadership role of employee performance through motivation. The technique of collecting data using interviews , questionnaires and observations . The population in this study are permanent employees of the marketing part of PT . Indo Putra Sejahtera of 40 people . The total sample of 40 respondents , using sensus sampling the determination samples when all members of the populasi used as a sample. Analysis of the data used is the linear regression analysis and significance test with SPSS for Windows. The conclusion from this study is there is significant influence role of leaders on employee performance through motivation as an intervening variable in PT . Indo Putra Sejahtera. Dari results of this study indicate that the variable role of leader on the motivation and the role of the leader is able to explain the motivation sebasar 38.1 % . Variable role of leader affect the performance of employees and the role of the leader is able to explain the performance of employees is 40.9%. Motivation variable influence on employee performance and motivation are able to explain the performance of employees amounted to 36.3 % . Together the role of leader and motivational variables affect the performance of employees so that the role of leader and motivation are able to explain the performance of employees amounted to 47.8 % . Then in the path analysis , there is the influence of mediation or motivation to work in the relationship intervening role of leader on employee performance . The conclusion is that if the leadership role enhanced the performance of employees would be better to increase employee motivation .